2013
DOI: 10.1002/gcc.22116
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological impact of VHL, PBRM1, BAP1, SETD2, KDM6A, and JARID1c in clear cell renal cell carcinoma

Abstract: VHL is mutated in the majority of patients with clear cell renal cell carcinoma (ccRCC), with conflicting clinical relevance. Recent studies have identified recurrent mutations in histone modifying and chromatin remodeling genes, including BAP1, PBRM1, SETD2, KDM6A, and JARID1c. Current evidence suggests that BAP1 mutations are associated with aggressive disease. The clinical significance of the remaining genes is unknown. In this study, targeted sequencing of VHL and JARID1c (entire genes) and coding regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 68 publications
4
98
1
Order By: Relevance
“…Previous studies indicated that SETD2 mutation occurred in 3-12% of sporadic ccRCC patients, which ranked second of the most frequent gene mutations in ccRCC next to VHL gene mutation (17). In our present study, IHC staining revealed that SETD2 was positively expressed in the cell nucleus of all normal renal tubular tissues.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies indicated that SETD2 mutation occurred in 3-12% of sporadic ccRCC patients, which ranked second of the most frequent gene mutations in ccRCC next to VHL gene mutation (17). In our present study, IHC staining revealed that SETD2 was positively expressed in the cell nucleus of all normal renal tubular tissues.…”
Section: Discussionsupporting
confidence: 65%
“…12 The deletion or mutation of BAP1 is associated with high tumor grade and poorer prognosis. [15][16][17][18] Following prior investigations for image-based inference of gene mutation status in glioblastoma multiforme brain tumors, lung, and breast tumors, we sought to investigate if BAP1 mutation status can be detected based on computationally derived volumetric and textural image features of the primary tumor from contrast enhanced renal CT scans of these patients. In this paper, we present an imaging-genomic pipeline to extract three-dimensional image features and correlate them with molecular data associated with the disease.…”
Section: Renal Cell Carcinomamentioning
confidence: 99%
“…Mutation of VHL alone is not sufficient to cause RCC cases 13 . Recently, large scale targeted and whole exome sequencing studies of RCC have identified other frequently mutated genes including polybromo 1 (PBRM1) and SET domain containing 2 (SETD2) 13 . The PBRM1 is a tumor suppressor gene, located on the short (p) arm of chromosome 3 at position 21 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Classically, RCC is characterized by inactivation of the VHL tumor suppressor gene in the majority of cases [11][12][13] . Mutation of VHL alone is not sufficient to cause RCC cases 13 .…”
Section: Introductionmentioning
confidence: 99%